Attachment and mental health in families of native people: A cross-sectional study - Bautista Valdivia, Jhonny (2024)
Background: Globally, 13% of children experience a mental disorder. Mental health problems in infancy are closely related to attachment, which serves as the primary bond within the family and forms the basis for personality development and mental health. In Mexico, research on infant mental health is limited. Objective: To determine the relationship between attachment styles and family mental health in indigenous populations from the southern Huasteca region of San Luis Potosí, Mexico. Method: A cross-sectional, descriptive, analytical, and correlational study. The study utilized the Reporting Questionnaire for Children (RQC), Self-Report Questionnaire (SRQ), Attachment Styles Classification Questionnaire (ASCQ), and Mental Health in Primary Care (MHQPHC). Results: The sample included 179 families with children aged 6 to 12. Sampling was conducted by appointment, selecting 35 families per locality; 58% of participants belonged to Indigenous communities, 92% were Nahuatl, and 2% were Tenek. Families from indigenous communities showed higher levels of avoidant attachment. Also, a significant relationship was identified between avoidant attachment and child mental health. A strong association was observed between the mental health of parents and children. Conclusions: Indigenous families experience disruptions in secure attachment processes due to migratory labor demands, leading to avoidant attachment styles.